Vlog Quality, Engagement Level, and Purchase Intention: Analysis of Information Value Mediation in Digital Marketing - Dera Tamaharani; Siska Ernawati Fatimah (Mabsya: Jurnal Manajemen Bisnis Syariah, 2026)
This study aims to analyze the influence of vlog quality and engagement level on purchase intention, as well as to examine the role of information value as a mediating variable in this relationship within the local cosmetic industry. A quantitative approach with an explanatory research design was employed. Purposive sampling was used to involve 190 respondents from Generation Z and Millennials who watch Hanasui videos. Data were collected using a Likert-scale questionnaire distributed online in Cirebon City. Structural analysis was conducted using PLS-SEM with SmartPLS. The findings indicate that vlog quality does not directly influence purchase intention; however, information value and engagement level are the two primary factors that significantly influence purchase intention. These findings emphasize that, to encourage consumers to make purchases, video content must present valuable and relevant information. This study adopts a content marketing approach for local cosmetic SMEs, which can drive digital economic growth, enabling companies to increase sales and strengthen brand competitiveness in the social media market through data accuracy and building emotional bonds with consumers. The novelty of this research lies in the use of information value as a mediating variable that bridges vlog quality and engagement level with purchase intention. This study offers a new contribution: vlog quality and engagement levels, when combined with high-quality information, influence purchase intention, particularly among Generation Z and Millennials.